Genetic signature of human longevity in PKC and NF‐κB signaling. Issue 7 (1st July 2021) - Ryu, Seungjin; Han, Jeehae; Norden‐Krichmar, Trina M.; Zhang, Quanwei; Lee, Seunggeun; Zhang, Zhengdong; Atzmon, Gil; Niedernhofer, Laura J.; Robbins, Paul D.; Barzilai, Nir; Schork, Nicholas J.; Suh, Yousin
Abstract: Gene variants associated with longevity are also associated with protection against cognitive decline, dementia and Alzheimer's disease, suggesting that common physiologic pathways act at the interface of longevity and cognitive function. To test the hypothesis that variants in genes implicated in cognitive function may promote exceptional longevity, we performed a comprehensive 3‐stage study to identify functional longevity‐associated variants in ~700 candidate genes in up to 450 centenarians and 500 controls by target capture sequencing analysis. We found an enrichment of longevity‐associated genes in the nPKC and NF‐κB signaling pathways by gene‐based association analyses. Functional analysis of the top three gene variants ( NFKBIA, CLU, PRKCH ) suggests that non‐coding variants modulate the expression of cognate genes, thereby reducing signaling through the nPKC and NF‐κB. This matches genetic studies in multiple model organisms, suggesting that the evolutionary conservation of reduced PKC and NF‐κB signaling pathways in exceptional longevity may include humans. Abstract : To test the hypothesis that variants in genes implicated in cognitive function may promote exceptional longevity, we performed a 3‐stage study to identify functional longevity‐associated variants in ~700 candidate genes in up to 450 centenarians and 500 controls by target capture sequencing analysis. We found an enrichment of longevity‐associated genes in the nPKC and NF‐kB signaling pathways by gene‐based association analyses. Functional analysis of the top three gene variants (NFKBIA, CLU, PRKCH) suggests that non‐coding variants reduce signaling through the nPKC and NF‐kB.